Close Connection Between Words and Culture - Sashka Jovanovsk (Zien Journals, 2021)
Sociolinguistics may be defined as “the study of how language is used by different groups in society.” Of the same importance for this area of linguistics, however, is the focus on the language and the culture in which it is spoken, and the relationship between the two has been an area of interest for many researchers. The statement that such a connection exists is now of little doubt and the relationship may be manifested in many areas of social usage of the language.
Keywords: Culture; words; kinship; relationship